Overexpression of the Rice SUMO E3 Ligase Gene OsSIZ1 in Cotton Enhances Drought and Heat Tolerance, and Substantially Improves Fiber Yields in the Field under Reduced Irrigation and Rainfed Conditions. (1st March 2017) - Mishra, Neelam; Sun, Li; Zhu, Xunlu; Smith, Jennifer; Prakash Srivastava, Anurag; Yang, Xiaojie; Pehlivan, Necla; Esmaeili, Nardana; Luo, Hong; Shen, Guoxin; Jones, Don; Auld, Dick; et al.
Abstract : The Arabidopsis SUMO E3 ligase gene AtSIZ1 plays important roles in plant response to abiotic stresses as loss of function in AtSIZ1 leads to increased sensitivity to drought, heat and salt stresses. Overexpression of the AtSIZ1 rice homolog, OsSIZ1, leads to increased heat and drought tolerance in bentgrass, suggesting that the function of the E3 ligase SIZ1 is highly conserved in plants and it plays a critical role in abiotic stress responses. To test the possibility that the SUMO E3 ligase could be used to engineer drought- and heat-tolerant crops, the rice gene OsSIZ1 was overexpressed in cotton. We report here that overexpression of OsSIZ1 in cotton results in higher net photosynthesis and better growth than wild-type cotton under drought and thermal stresses in growth chamber and greenhouse conditions. Additionally, this tolerance to abiotic stresses was correlated with higher fiber yield in both controlled-environment and field trials carried out under reduced irrigation and rainfed conditions. These results suggest that OsSIZ1 is a viable candidate gene to improve crop yields under water-limited and rainfed agricultural production systems.